Analysis of Factors Influencing Customers' Decision to Choose Saving - Jamila, Khaidar Rahmaini (Journal of Islamic Economic Scholar, 2020)
The purpose of this study is to find out what factors influence the customer's decision in choosing BNI Syariah Tunas Hasanah iB savings account in Medan also to see which variable is dominant in the customer's decision to save. This research method uses quantitative methods, with data collection techniques that are distributing questionnaires to customers of BNI Syariah Medan. The data collected was processed using SPSS application version 16. The results showed that the dependent variable with various factors affecting it was 83.5% able to be explained by (variable X) product quality, promotion and service, while the remaining 16.5% customer decisions were explained by other causes outside of research. Each of the X variables has a significant effect on the customer's decision to choose iB Tunas Hasanah savings.Keywords : Product Quality, Service, Promotion, Sharia Bank